102 Demonstrating how being available for advice enhances patient care. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Tempest, Emma
Abstract : Background: The medical team are available for clinical advice 24 hours a day to Hospice staff, Hospital staff and HCP based in the community. They also advise patients, family or carers directly. Doctors may be asked for advice during any work activity even if it is unrelated to the enquiry. The role of advice is less visible than other patient contacts and therefore risks being undervalued. Methodology: The team recorded advice given over a 5 week period excluding whilst on call. Results: 151 pieces of advice given. Mean 6 pieces per day (range 0–21). 81% were dealt with within 30 minutes. The longest episode was 2.5 hours. This does not include the time taken if a home visit was needed. The episodes amounted to 77 hours 20 minutes. Mean 3 hours per day (range 0–11.5). 81% of advice is given to Hospice staff with Community CNS's being the largest single group. We took enquiries from a wide range of sources. 68% patients were already known to the hospice. Most advice given was around symptom control. Other advice included psychiatric symptoms, diagnosis/prognosis, bereavement, supporting families, genetic testing, making best interest decisions, ethical dilemmas, admissions, discharges, obtaining medications and completing death certificates. No request was inappropriate. 6 hospital admissions were directly avoided. In 7 cases an urgent home visit was done by the medical team. The majority of patients remained in their care setting. Only one patient was admitted to hospital. Conclusion: Being available for advice has a direct impact on patient care and should be recognised as an efficient way of influencing the management of a large number of patients. It is an opportunity to support whoever is asking the advice. If advice was not sought the patient may have ended up in the acute hospital due to sub-optimal management.